The communication skills of the geography teachers in the preparatory stage and their relation to their mental abilities (Journal of the College of Basic Education, 2022)
The research aims at learning the communication skills of the geography teachers in the preparatory stage and their relation to their mental abilities. The researcher relied on the descriptive approach and a number of procedures which included defining the research society, which was limited to the teachers of geography in the preparatory stage (morning study) in the Directorate of Education of Rusafa third for the academic year 2017-2018. (94) teachers and schools, and the sample of the current research included (60) teachers and schools of them. To achieve the objectives of the research, the researcher adopted two tools: observation card to measure communication skills, which consisted of (30) paragraphs divided into two areas (verbal communication skills and non-verbal communication skills) and mental abilities test consisting of (80) (Linguistic ability, numerical ability, spatial capacity and explanatory capacity). The researcher used the statistical bag to analyze the results. After completing the presentation and interpretation of the results of the research, the researcher concluded: The teachers of geography in the middle stage have a medium level of communication skills and have an average level of mental abilities, and found a relationship between communication skills and mental abilities, In the light of the research results and conclusions, the researcher recommended a number of recommendations and suggestions